Penyuluhan Peran Laboratorium dan Pentingnya Praktikum dalam Pembelajaran Fisika - Sutrio Sutrio; Gunawan Gunawan; Lovy Herayanti; Nina Nisrina (Indonesian Publication Center, 2023)
This community service activity aimed to enhance the understanding of prospective physics teachers regarding the role of laboratories and the importance of practical work in physics learning. The event involved 40 students currently undergoing education to become physics teachers. The activities were conducted through interactive lectures and laboratory practical sessions. The lectures provided in-depth information about the role of laboratories in physics education, explored the benefits of practical work as a means of applying theoretical concepts in real-life situations, and identified potential challenges in implementing practical work in schools. The laboratory practical sessions offered direct experiences for students to apply the physics concepts learned in the classroom. The results of this activity demonstrated a significant improvement in the understanding of prospective physics teachers regarding the role of laboratories and the importance of practical work in learning. Thus, this activity contributes positively to enhancing the quality of physics education at the primary and secondary education levels.